Spacecraft attitude control using non–singular finite time convergence fast terminal sliding mode. (16th April 2013) - Tiwari, Pyare Mohan; Janardhanan, S.; Masuq–un–Nabi,
In this work, a finite time convergent, non–singular continuous time sliding mode controller is proposed to control the attitude of rigid spacecraft. The proposed controller is derived using non–singular fast terminal sliding mode (NFTSM) with power rate reaching law. The fast convergence with finite time stability is ensured both in reaching phase as well in sliding phase, and is proved using Lyapunov–type theorem. The effectiveness of proposed controller is verified by numerous simulation results. The results show that attitude control system is made globally stable and robust enough to negate model uncertainties, bounded disturbances, and actuator saturation problems with a control input of continuous nature.